An investigation of the mechanical fatigue behavior of low thermal expansion lattice structures. (December 2015) - Mercer, C.; Lee, J.; Balint, D.S.
Graphical abstract: Highlights: A study of the fatigue behavior of a low thermal expansion lattice was conducted. The fatigue behavior of the lattice is markedly inferior to that of the parent alloy. Analytical tools were developed to predict the fatigue lives of such lattices. Abstract: A study of the mechanical fatigue behavior of a Ti–6Al–4V lattice structure designed to exhibit controlled thermal expansion has been performed. Comparison of S – N curves generated under both zero-tension and fully reversed cyclic loading has determined that the fatigue resistance of the lattice is substantially poorer than that of the constituent Ti–6Al–4V material for the same remote applied (macroscopic) stress. In addition, the effect of beta annealing the as-received mill-annealed alloy was also to reduce fatigue life in both the lattices and parent material. This effect is due to significant microstructural changes that occurred during heat treatment. Increasing the stress ratio ( σ min / σ max ) of the cyclic waveform from −1 to 0 had a similar effect. An analytical model has been developed to predict the fatigue life of the lattice structures from the S – N curves of the parent material, by determining the relationship between the macroscopic stresses acting on the lattice structure and the local stresses. The local stresses were then used in a multiaxial fatigue model to determine the fatigue life. The analytical model is able to predict the fatigue life with reasonable accuracy and minimal cost. The Findley multiaxial fatigue parameter for the parent material and lattice structures can be fitted with a power law equation and appears to fall onto a single curve, suggesting the local behavior within the lattice material is similar to the parent material. The analytical tools developed in this study can be hugely beneficial to the design of these lattice structures in the aerospace and communications industries.